MACROECONOMIC FACTORS & ASSET PORTFOLIO THEORY IN IDX30: STOCK RETURNS 2013-2020 - Harsanico, Andreas Billyarta; Sugiyanto, Fx. (EP FEB UNS, 2023)
This study examines the influence of macroeconomic factors on stock returns within Indonesia's IDX30 index, the nation's leading stock index. The primary aim is to evaluate both short-term and long-term impacts of these macroeconomic variables on stock market returns, guided by Milton Friedman's theoretical framework. The research utilizes Ordinary Least Squares (OLS) to assess immediate relationships and Vector Error Correction Model (VECM) to capture long-term dynamics. The study analyzes historical data from the IDX30, focusing on variables such as inflation rates, interest rates, and GDP growth as key indicators. Results indicate that specific macroeconomic factors, particularly interest rates and inflation, have significant effects on IDX30 stock returns. In the short term, interest rates exhibit a strong inverse relationship with stock returns, while in the long term, GDP growth positively correlates with stock market performance.